Effect of Educational Intervention using Video Role-playing on Nursing Students Perceived Civility-Incivility - Pranatalia, Fedora; Arnolus, Stefen Ista; Simorangkir, Tasya Stefani Br; Eka, Ni Gusti Ayu; Purimahua, Dora Irene (Journal of Health Education, 2024)
Background: This study aimed to examine the effect of educational intervention using video role-playing on the knowledge of civility among second-year nursing students at a private faculty of nursing. Methods: This study employed a quasi-experimental design using pre-post approach. A total of 148 nursing students completed the intervention. The educational intervention consisted of 60 minutes-online learning, including watching video role-plays and discussions. This study applied a paired t-test for data analysis. Results: There was a significant effect before and after the educational intervention. Before the intervention, few respondents reported their perceived civility were under uncivil and mildly civil categories. After the intervention, all respondents perceived their civility were moderate to highly civility. Conclusions: Video-based educational intervention significantly affects students' perceived civility